Peningkatan Peran Orang Tua Dalam Mendukung Pembelajaran Anak Di Rumah - Hendrikus Torimtubun; Kusnanto Kusnanto; Usman Usman; Tjia Chiu Ha (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
The role of parents in supporting children's learning at home is very important to improve the effectiveness of education. However, many parents still experience difficulties in implementing appropriate learning strategies, lack of time, and lack of understanding of effective teaching methods. The objectives are: Increase parents ‘understanding of effective learning methods at home, assist parents in managing time between work and children's learning assistance, improve parents’ pedagogical skills, Encourage better communication between parents and teachers in supporting children's development, Increase children's learning motivation through interest-based learning strategies and a supportive environment. The implementation method consists of four stages, including: Parent Training, Mentoring and Consultation, Making Learning Materials, Evaluation and Monitoring. Outputs to be achieved are: Increased awareness and skills of parents in supporting children's learning at home, better cooperation between parents and schools in creating a conducive learning environment, increased motivation and academic achievement of children.